Willingness to pay for a pharmacist’s dispensing service: a cross-sectional pilot study in the state of Penang, Malaysia - Shafie, Asrul A. (Centro de Investigaciones y Publicaciones Farmaceuticas, 2010)
OBJECTIVE: The aim of this pilot study was to assess the value of the dispensing service of pharmacists from the general public’s perspective using the contingent valuation technique in the State of Penang, Malaysia. METHODS: Participants were conveniently sampled from malls and were given a self-completed questionnaire that collected the patient’s demographic information and their knowledge about the pharmacist’s dispensing service. They were then presented with a description of the pharmacist’s dispensing service, the risk of medication errors in prescriptions and their consequences, and the risk reduction of medication errors associated with pharmacist intervention. The willingness to pay (WTP) of the participants was later assessed using a contingent valuation interview that asked the likelihood and maximum amount they were willing to pay. RESULTS: In the study, 100 people participated, and 57% were aged between 18 and 35 years. Of these participants, 51% were women, and 46% of them earned more than 1000 MYR (285.71USD) per month. In addition, 8% of the participants had never visited a community pharmacy. Finally, 67% of the participants were willing to pay for the pharmacists’ dispensing service, and the median amount that the participants were willing to pay was 10 MYR (2.86USD). The WTP amount was moderately correlated with their knowledge of the community pharmacist’s dispensing services (r=0.377, p=0.02). CONCLUSION: Generally, the public valued the pharmacist’s dispensing service. Their acceptance can be further improved by educating the public on the role of the pharmacist.